Study on the printing quality of fused deposition modeling using Taguchi method. Issue 1 (1st September 2022) - Teng, H M; Fan, S K; Jiang, C H; Yang, Q W; Liu, F H; Tsao, C C
Abstract: Fused deposition modeling (FDM) in 3D printing is a very promising technology and one of the focuses of scientific research. The main reason is that it has the advantages of simple structure, relatively low price and convenient operation, which has made its development more and more rapid in recent years. However, due to the fact that the FDM products are susceptible to the operating environment, the printing quality is not stable enough and the development is restricted. In addition, this research uses Taguchi method to explore FDM to optimize a long and thin desired volume of the workpiece under different printing parameters (printing temperature, printing speed ratio, and printing layer thickness). From the experimental results, the size of the factors that affect the FDM's expected volume of the workpiece is, in order, the printing temperature is the most important, the printing speed ratio is the second, and the printing layer thickness is the smallest. The optimal parameter combination for the desired workpiece volume is A1 B1 C1, that is, the printing temperature is 190°C, the printing speed ratio is 0.286 (20 mm/s on the outer side, 70 mm/s on the inner side), and the printing layer thickness is 0.1 mm. Finally confirmed the experimental results and found that the volume error of the finished product using the best printing parameters is less than 0.3 %, which proves that the optimized printing parameters obtained by Taguchi method are indeed effective and feasible.